Selective and Efficient Synthesis of Pine Sterol Esters Catalyzed by Deep Eutectic Solvent - Honggang Shi; Zeping Lu; Huajin Xu; Shushu Wang; Binbin Nian; Yi Hu (Molecules, 2023)
Phytosterol esters have attracted widespread academic and industrial interests due to their advantages in lowering cholesterol, as antioxidants, and in preventing or treating cancer. However, the generation of by-products limits the application of phytosterol esters in food fields. In this study, deep eutectic solvents (DESs), a series of green, nontoxic, low-cost and biodegradable solvents, were adopted as the catalyst for the synthesis of pine sterol esters. The results showed that the acidic DES which was prepared with choline chloride (ChCl) and p-toluene sulfonic acid monohydrate (PTSA) with a molar ratio of 1:3 performed best in the prescreening experiments. To further improve the efficiency of the pine sterol ester, the molar ratio of substrates, the amount of catalyst, the reaction temperature and the reaction time were optimized, and its yield was improved to 94.1%. Moreover, the by-products of the dehydration side reactions of the sterol can be efficiently inhibited. To make this strategy more universal, other fatty acids were also used as the substrate for the synthesis of pine sterol esters, and a yield of above 92.0% was obtained. In addition, the reusability of DES was also investigated in this study, and the efficiency of DES was well maintained within five recycled uses. Finally, DFT calculations suggested that the suitable H-bonds between ChCl and PTSA decreased the nucleophilic capacity and increased the steric hindrance of the latter, and further prevented the attack on βH and reduced the generation of by-products. This study developed a reliable and eco-friendly strategy for the preparation of high-quality phytosterol esters with low-dosage catalyst usage and high selectivity.